English Pronunciation in the Eighteenth and Nineteenth Centuries - Jones, C. author. aut Link
XI, 402 p.
Keywords: This work provides a detailed account of word level pronunciation in England and Scotland between 1700 and 1900. All major and minor source materials are presented in depth and there is a close discussion of contemporary attitudes to pronunciation standards and orthographic reform. The materials are presented in three chronological periods: 1700-1750, 1750-1800 and the Nineteenth century, so that the reader is able not only to see the main characteristics of the pronunciation of both vowels and consonants in each period, but can also compare developments from one period to another, thus identifying ongoing changes to the phonology.